2016
DOI: 10.18869/acadpub.hms.22.2.95
|View full text |Cite
|
Sign up to set email alerts
|

Teratogenic Effects of Hydroalcoholic Extract of Capparis spinosa Leaf on Balb/c Mice

Abstract: Aims: As a medical herb, Capparis spinosa is used in the traditional medicine. Nevertheless, its side-effects are not yet studied, especially during the pregnancy. The aim of this study was to investigate the tratogenic effects of hydro-alcoholic extract of the leaves of Capparis spinosa on the embryo of Balb/c mice. Materials & Methods: In the experimental method, 32 pregnant Balb/c mice were randomly divided into four groups including control and experimental groups. The experimental groups were the groups r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…C. spinosa is used in traditional medicine since ancient times and it is alleged to show antioxidant and antibacterial effects 6 . Studies on the effects of this medicinal plant during pregnancy are close to nonexistent, one study by Davari et al 7 suggested the possibility of teratogenic potential of C. spinosa after conducting their study on pregnant mice. We theorize the effect of C. spinosa on neural tube formation and development, and we suggest for more research to be done on the subject.…”
Section: Clinical Discussionmentioning
confidence: 99%
“…C. spinosa is used in traditional medicine since ancient times and it is alleged to show antioxidant and antibacterial effects 6 . Studies on the effects of this medicinal plant during pregnancy are close to nonexistent, one study by Davari et al 7 suggested the possibility of teratogenic potential of C. spinosa after conducting their study on pregnant mice. We theorize the effect of C. spinosa on neural tube formation and development, and we suggest for more research to be done on the subject.…”
Section: Clinical Discussionmentioning
confidence: 99%